Fertirrigation with sugarcane vinasse: Foreseeing potential impacts on soil and water resources through vinasse characterization - Fuess, Lucas T.; Rodrigues, Isabella J. [UNESP]; Garcia, Marcelo Loureiro [UNESP] (Taylor & Francis, 2017)
This paper reports the characterization of the polluting potential of sugarcane vinasse, the main wastewater from ethanol production. Compositional data from vinasse samples collected from sugarcane biorefineries were used to predict negative effects on the soil, water resources and crops potentially associated with fertirrigation, the primary final destination of vinasse in Brazil. High risks of soil salinization were associated with the land disposal of vinasse, as evidenced by the high levels of total dissolved solids (TDS; >4,000 mg L−1) and electrical conductivity (>6.7 dS m−1). The high TDS levels coupled with the high biodegradable organic content of vinasse (>14 g L−1) also favor organic overloading events, leading to local anaerobiosis conditions. Conversely, soil sodification should not be observed in areas fertirrigated with sugarcane vinasse, given the low Na concentrations (<66 mg L−1) relative to Mg (>145.1 mg L−1) and Ca (>458.4 mg L−1) levels. Priority pollutants (Cu, Cr, Ni, Pb and Zn) and phytotoxic elements (Al and Fe) were also found in the analyzed samples; however, relevant environmental impacts should not be associated with these particular constituents. Overall, the relatively simple methodology used herein could efficiently replace massive field data collection to provide a basic understanding of the fate of vinasse in the environment in order to highlight the priority points to be considered in the management of this effluent. In summary, the prompt implementation of treatment plants in distilleries, in addition to a continuous and broad compositional characterization of vinasse, is essential to guarantee its adequate reuse.
Keywords: Fertirrigation; negative effects’ prediction; polluting potential; priority pollutants; sugarcane biorefinery; vinasse management